Status sosio-Ekonomi kaum suluk di pekan semporna : Satu tinjauan terhadap keadaan kemiskinan - Mohammad Ahad, Abdul Laja (Universiti Malaysia Sarawak (UNIMAS), 1997)
The general purpose of this study is to determine the socio-economic status of in relation to poverty problems among The Suluk Community at Pekan Semporna. The specific objective is to determine the level of income, socio-economic background (Land ownership, level of education, family size and types of jobs), and the relationship between economic activities with their level of poverty. Seventy respondents from Kampung Kubang Pinang 2 were selected using systematic random sampling. Data were collected by interviewing the respondent using one set of questionnaire. A translator was engaged when necessary. Analyses of data were made in the relation to the objective and hypothesis of the study. The statistical tools used were mainly Chi-Square test, Pearson Product-Moment Correlation and Cross tabulation. This study found that 75.4% of respondents were farmers and fishermen, earning income less than RM350.00 per month (the verge of poverty). Besides, this study show that, 67.1 % of the respondents had less form 3 education and 24% of the respondents had never received formal education. On the whole, the findings seemed to partially support the framework which the variables and hypothesis were developed. Test of hyphoteses indicate significant relationship between income and level of education and types of jobs. It can be implied that the low level of education and the types of jobs influence the level low of income, and hence poverty among The Suluk Community.